Bioimpedance in Biomedical Applications and Research - Simini, Franco; Bertemes-Filho, Pedro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is based on the best contributions to the advancement of bioimpedance knowledge and use from the Latin American Congress series, CLABIO. Basic bioimpedance facts as well as promising and original contributions to bioimpedance theory and applications are presented, giving the reader stimulating material for reflection, decision making, and further experiments. Contributions come from a diverse international pool of experts and address topics on electrode and skin impedance modelling, tomography, spectroscopy, instrumentation, and clinical applications.
Chapter 1. Introduction -- Chapter 2.Electrical Impedance Spectroscopy -- Chapter 3.Basic Electrical Impedance Tomography -- Chapter 4.Electrical Impedance Tomography to Detect Trends in Pulmonary Edema -- Chapter 5.Electrical Impedance Signal Analysis for Medical Diagnosis -- Chapter 6.Tissue Engineering Instrumentation based on Electrical Impedance Measurements -- Chapter 7.Basics of Numerical simulations of bioimpedance phenomena -- Chapter 8.Numerical basics of bioimpedance measurements -- Chapter 9.Focused Impedance Method: basics and applications -- Chapter 10.Clinical Applications of Electrical Impedance Spectroscopy -- Chapter 11.Body Composition by Bioelectrical Impedance Analysis -- Chapter 12.Bioimpedance for Analysis of Body Composition in Sports -- Chapter 13. Wavelet Analysis in Impedance Spectral Rheocardiography.
Keywords: Biomedical engineering; Biophysics; Spectrum analysis; Radiology; Biomedical Engineering and Bioengineering; Biophysics; Spectroscopy; Radiology